2013
DOI: 10.1016/j.ejmech.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, local anaesthetic and antiarrhythmic activities of N-alkyl derivatives of proline anilides

Abstract: We describe here the design, synthesis and evaluation of in vivo local anaesthetic and antiarrhythmic activities of a series of N-alkylproline anilides. Most of the compounds demonstrated surface anaesthetic activity higher than that of lidocaine, ropivacaine and bupivacaine. We established that the local anaesthetic activity was sensitive to structural variations in the substitution pattern at the aromatic ring and the type of alkyl group at the proline nitrogen atom. Some of the prepared N-alkylproline anili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…So; The classical substitution pattern on the aromatic ring of LAs includes; a methyl group (e.g., prilocaine), two methyl groups (e.g., lidocaine, bupivacaine, and ropivacaine), and sometimes three methyl groups (e.g., trimecaine, cyclomecaine, and pyromecaine). However, unlike the local anesthetic activity, it has been proposed that the antiarrhythmic properties of the compounds tolerate various types of substituents on the phenyl ring, obtaining homologous compounds with less toxicity than the classic ortho-methyl substituted (lidocaine, bupivacaine and ropivacaine) [14,27]. Based on these characteristics, the pharmacophore was established (Figure 4) using Maestro Schrodinger 11.8, identifying the most important pharmacophore characteristics in Las.Thus, (1) a hydrophobic domain formed by the alkyl substituents of the aromatic domain was identified; (2) a hydrogen donor domain of the amide nitrogen; (3) a hydrogen acceptor, the carbonyl oxygen of the amide; (4) a cation-forming domain, the nitrogen of the tertiary amine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So; The classical substitution pattern on the aromatic ring of LAs includes; a methyl group (e.g., prilocaine), two methyl groups (e.g., lidocaine, bupivacaine, and ropivacaine), and sometimes three methyl groups (e.g., trimecaine, cyclomecaine, and pyromecaine). However, unlike the local anesthetic activity, it has been proposed that the antiarrhythmic properties of the compounds tolerate various types of substituents on the phenyl ring, obtaining homologous compounds with less toxicity than the classic ortho-methyl substituted (lidocaine, bupivacaine and ropivacaine) [14,27]. Based on these characteristics, the pharmacophore was established (Figure 4) using Maestro Schrodinger 11.8, identifying the most important pharmacophore characteristics in Las.Thus, (1) a hydrophobic domain formed by the alkyl substituents of the aromatic domain was identified; (2) a hydrogen donor domain of the amide nitrogen; (3) a hydrogen acceptor, the carbonyl oxygen of the amide; (4) a cation-forming domain, the nitrogen of the tertiary amine.…”
Section: Resultsmentioning
confidence: 99%
“…As is stated before, it has been suggested that compounds with the ability to block TASK-1 channel could become an innovative strategy for the treatment of AF [21], as is the case of LAs. Because it is possible to define the chemical characteristics required for a ligand to be active against a certain target, for example, a functional group important for ligand-protein interactions, such as a hydrogen bond acceptor (HBA) group or a positive charge center [22,23], it arises the necessity to propose the rational design of new compounds based on the common structural characteristics of LAs: lidocaine, bupivacaine and ropivacaine taking into account their ability to act as antiarrhythmic agents through the blockade of the TASK-1 channel [12][13][14][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of drug development, the development of local anesthetics and antiarrhythmic drugs is usually studied and developed simultaneously. In 2013, Kalinin D. V. et al 65 reported the synthesis and biological activity of N -alkyl derivatives of proline aniline. In terms of synthesis, the designed synthetic route focused on two key biological activity substitutions of target compounds 4a–4p, and the substitutions of the tetrahydropyrrole ring and benzene ring ( Scheme 4 ).The bromination of 5-chloropentanoic acid (compound 1) was accomplished by the action of bromine with phosphorus trichloride to produce 2-bromo-5-chloropentanoic acid.…”
Section: Synthesis and Biological Activitiesmentioning
confidence: 99%
“…Local anesthetic (LA) compounds, such as lidocaine, ropivacaine, and bupivacaine (Figure 1), are used as antiarrhythmics drugs in clinical practice [35,36] and were shown to have multiple mechanisms of action [36]. Ropivacaine and bupivacaine block https://doi.org/10.26434/chemrxiv-2024-v70lj ORCID: https://orcid.org/0000-0002-3542-7528 Content not peer-reviewed by ChemRxiv.…”
Section: Introductionmentioning
confidence: 99%